‘It put me in their shoes’: challenging negative attitudes towards asylum seekers among Australian children - Hartley, Lisa; Fleay, Caroline; Pedersen, Anne; Cook, Alison; Jeram, Alenka (2021)
This paper evaluates a short school-based intervention run by Australian Red Cross, designed to reduce children’s prejudice towards asylum seekers. A total of 121 children aged between 10 to 12 in four schools in Perth, Western Australia, completed questionnaires at Time 1 (pre-intervention), Time 2 (immediately after the intervention), and Time 3 (8-9 months after the intervention). The intervention used a mixture of approaches: providing information, encouraging empathy, making positive social norms more explicit, and fostering imagined contact with asylum seekers. The intervention content was also reinforced by teachers throughout the school year. The study found that the intervention was effective in increasing the children’s positivity towards asylum seekers, reducing prejudiced attitudes, and increasing intentions to interact with asylum seekers. It also found that the intervention increased the children’s accuracy in defining ‘asylum seeker’ and ‘refugee’. These results occurred both in the short-and long-term, although there was some regression over time.